ANÁLISE DO SISTEMA DE CERTIFICAÇÃO AMBIENTAL AQUA FRENTE ÀS DIMENSÕES DA SUSTENTABILIDADE - Gonçalves, Maximiliano; Tiburcio, Tulio M S (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The construction industry, one of the sectors that generates a large number of jobs in Brazil, is also the one that generate most waste. Besides, it is the sector responsible for large environmental impacts, requiring, in the current scenario, alternative proposals such as sustainable buildings. Within this context, certifications have been created to evaluate the sustainability performance of buildings. However, some of these certifications are of international origin and there are some inadequacies when applied in the Brazilian scenario. Because it is a country of continental dimensions, Brazil has tropical characteristics and several bioclimatic zones. The AQUA certification system presents itself as an initiative to meet Brazilian standards. This paper aims to analyse the AQUA certification system within six dimensions of sustainability: environmental, social, cultural, economic, spatial and technological. It search to understand the criteria and the evaluation methods of this certification, verifying and identifying how they address these six dimensions of sustainability. Results show that the AQUA system has a more holistic approach considering sustainability dimensions.